Babao Dan decreases hepatocarcinogenesis by inhibiting hepatic progenitor cells malignant transformation via down-regulating toll-like receptor 4 - Liang, Lei; Zhang, Lu-Yao; Liu, Wen-Ting; Zong, Chen; Gao, Lu; Li, Rong; Zhao, Qiu-Dong; Zhao, Na-Ping; Wei, Li-Xin; Zhang, Li; Han, Zhi-Peng (Frontiers in Oncology, 2023)
Babao Dan (BBD) is a traditional Chinese medicine that has been widely used as a complementary and alternative medicine to treat chronic liver diseases. In this study, we aimed to observe the effect of BBD on the incidence of diethylnitrosamine (DEN)-initiated hepatocellular carcinoma formation in rats and explored its possible mechanism. To verify this hypothesis, BBD was administrated to rats at a dose of 0.5g/kg body weight per two days from the 9th to 12th week in HCC-induced by DEN. 12 weeks later, we observed that DEN could induce hepatocarcinogenesis, and BBD could obviously decrease the incidence. The biochemical and histopathological examination results confirmed that BBD could protect against liver injury and decrease inflammatory infiltration. Our previous study has demonstrated that lipopolysaccharides (LPS) could increase ductal reaction and induce hepatic progenitor cells (HPCs) neoplastic transformation. Subsequently, immunohistochemistry staining results showed that BBD could effectively inhibit the ductal reaction and the expression of TLR4. In vitro, rat primary HPCs were induced for neoplastic transformation by LPS, and cultured with serum from BBD-treated rats (BBD-serum). The results showed that BBD-serum could obviously inhibit primary HPCs neoplastic transformation induced by LPS. The present study demonstrated that BBD could inhibit hepatocarcinogenesis via inhibiting HPC malignant transformation by regulating the TLR4/Ras/ERK signaling pathway.